2019
DOI: 10.1055/s-0039-1690724
|View full text |Cite
|
Sign up to set email alerts
|

Acetic Acid Catalysed One-Pot Synthesis of Pyrrolo[1,2-a]quinoxaline Derivatives

Abstract: An efficient acetic acid catalysed reaction has been developed for the synthesis of 4-aryl substituted pyrrolo[1,2-a]quinoxalines from readily available starting materials. A range of structures have been synthesised in very good to excellent yields. The one-pot reaction proceeds through imine formation, cyclisation followed by air oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Various synthetic pathways have been developed to prepare pyrroloquinoxalines [42][43][44] because it is crucial in drug discovery. For this reason, an efficient method was established by Allan et al [45], which is an acid-catalyzed reaction for the synthesis of 4-aryl substituted pyrrolo[1,2-a] quinoxalines (24). This one-pot reaction involves imine formation, followed by cyclization and air oxidation.…”
Section: Using the Catalytic Amount Of Acetic Acid And Aldehydesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various synthetic pathways have been developed to prepare pyrroloquinoxalines [42][43][44] because it is crucial in drug discovery. For this reason, an efficient method was established by Allan et al [45], which is an acid-catalyzed reaction for the synthesis of 4-aryl substituted pyrrolo[1,2-a] quinoxalines (24). This one-pot reaction involves imine formation, followed by cyclization and air oxidation.…”
Section: Using the Catalytic Amount Of Acetic Acid And Aldehydesmentioning
confidence: 99%
“…Xia et al [57] synthesized a series of penta-1,4-dien-3-one oxime comprising a quinoxaline moiety, equivalent to curcumin isolated from plant Curcuma Longa L. The synthesized compounds displayed antibacterial and antiviral activities, with distinct activity against TMV. As revealed in Scheme 13, 2-chloroquinoxaline (43) and penta-1,4-dien-3-one oxime ether (44) were stirred for 30 min and refluxed for 4 h at 80 • C to get the target compound (45). The product is recrystallized with acetonitrile and dichloromethane.…”
Section: Synthesis Of Penta-14-dien-3-one Oxime Containing a Quinoxaline Nucleus As Antiviral Agentsmentioning
confidence: 99%
“…In 2019, Patel et al reported an efficient acetic acid-catalyzed synthesis of pyrrolo[1,2- a ]quinoxalines 87 via a Pictet–Spengler type reaction of 2-(1 H -pyrrol-1-yl)aniline 78 to aldehyde 86 ( Scheme 28 ). 101 With only 10 mol% of AcOH acid as the catalyst, a total of 16 compounds were synthesized in 82–89% yields. Pleasingly, various substituted and unsubstituted 2-(1 H -pyrrol-1-yl)aniline 78 underwent the reaction smoothly to provide the desired product efficiently.…”
Section: Synthesis Of Fused Quinoxalines Based On Metal-free Two-comp...mentioning
confidence: 99%
“…The classical methods are the Bischler–Napieralski type reactions of N -(2-acylaminophenyl)-pyrroles using dehydrating reagents such as POCl 3 (Scheme 1A). 14 The most common methods are Pictet–Spengler type reactions between 2-(1 H -pyrrol-1-yl)anilines and cyclization partners such as aldehydes, 15 alcohols, 16 amines, 17 alkyl halides, 18 ketones, 19 1,3-diketones, 20 α-keto acids, 21 α-hydroxyl acids, 22 α-amino acids, 23 aryl acetic acids, 24 cyclic ethers, 25 and methyl arenes 26 in the presence of various oxidants (Scheme 1B). 27,28 Although these oxidants facilitated Pictet–Spengler type pyrrolo[1,2-α]quinoxaline synthesis, a high reaction temperature was usually required and the substrate scope was mostly limited to 4-aryl substituted pyrrolo[1,2-α]quinoxalines.…”
Section: Introductionmentioning
confidence: 99%